Influence of Karst Caves on the Pile’s Bearing Characteristics-A Numerical Study - Liang, Jia-hui; Fan, Qiu-yan; Qin, Kuo (Frontiers in Earth Science, 2022)
Compared with the amount of research undertaken on vertical-bearing piles in karst areas, there are fewer studies on the stability of horizontal-bearing piles (e.g., anti-slide piles and supporting piles), and little in the way of theoretical developments. At present, for the stability problem of horizontal-bearing piles in karst areas, the method of increasing the length of the pile to pass through the karst cave is generally adopted. However, the influence of the karst cave on the pile shaft is not considered. Based on this, this study used the ABAQUS finite element analysis software to carry out horizontal-loading numerical simulation tests for anti-slide piles where a karst cave is located in front of and under the pile. A five-factor and six-level orthogonal simulation test was designed, with the five parameters being the roof thickness of the karst cave in front of the pile, the distance between the karst cave in front of the pile and the pile shaft, the distance between the cave under the pile and the pile tip, the span height ratio of the cave in front of the pile, and the span height ratio of the cave under the pile. The displacement-load curves of each group of piles were inferred and the horizontal ultimate bearing capacity was determined. Finally, the statistical results were analyzed and tested by multiple linear regression to obtain a formula for the horizontal ultimate bearing capacity of an anti-slide pile considering two karst caves in its vicinity. The results of this work are of significance to the application of anti-slide piles in areas with karst caves.